The Art of Professing in Bourbon Mexico : Crowned-Nun Portraits and Reform in the Convent - Córdova, James M., 1974- (Book collections on Project MUSE., 2014)
"Offering a pioneering interpretation of the "crowned nun" portrait, this book explores how visual culture contributed to local identity formation in Mexico"--